Miocene deformation in the orogenic front of the Malargüe fold-and-thrust belt (35°30′–36° S): Controls on the migration of magmatic and hydrocarbon fluids - Barrionuevo, Matías (2019)
The integration of surface observations and sub-surface data (wellbore and seismic) from the orogenic front of the Malargüe fold-and-thrust belt allows us to study its kinematics and to interpret the local stress field and its control over fluid (magmatic and hydrocarbon) migration. Reverse faults correspond to inverted NNW-striking Mesozoic normal faults and N-S striking Cenozoic low-angle thrusts parallel to the orogen. Oblique structures with strike-slip movement are also present. The magmatic activity in the study area was strongly controlled by this structural framework and the in-situ stress field. Miocene dykes and sills were emplaced in relation to strike-slip and reverse faults, respectively. We propose an evolution of the study region from a foredeep sector, in the early-middle Miocene, to a peak in deformation in the late Miocene, and finally a waning of deformation from the Pliocene to the present. Our structural model suggests that during the evolution of the thrust front, the in-situ stress field changed from a compressional to strike-slip/compressional stress field, favouring the synchronous emplacement of sills and dykes. This alternation of stress regimes favours hydrocarbon migration through both thrusts and subvertical strike-slip faults. This exchange between both stress regimes is likely related to the similar values of the minimum (σ3) and intermediate (σ2) principal stress with an E-W oriented maximum principal stress (σ1) according to the plate convergence vector.